Poverty alleviation through access to land : highlights of discussion and summaries of technical papers circulated in the Policy Seminar on Access to Land, Denpasar, Bali, Indonesia, 22-28 October 1988 - Ahmed, Salehuddin, 1949-; Rahman, Shafiqur (CIRDAP study series ;, 1992)
With reference to South and Southeast Asian countries.